The Impact of Financial Management Practices on Firm Performance: A Study of the Manufacturing Sector in Indonesia - Rizka Ar Rahmah; Fred Ojochide Peter (PT Agung Media Publisher, 2024)
This study aims to examine the impact of financial management practices on the performance of firms operating in the manufacturing sector in Indonesia. In this study, we collected data from a number of manufacturing companies in Indonesia and analyzed the relationship between financial management practices and key performance indicators such as profitability, liquidity, and solvency. The findings of this study indicate that effective financial management practices have a positive impact on the performance of companies in the manufacturing sector in Indonesia. Disciplined and measurable budgeting practices have been shown to significantly contribute to increased profitability. Careful and regular financial analysis also helps companies identify performance trends, measure operational efficiency, and make better decisions. Furthermore, efficient working capital management practices have a positive impact on the liquidity of companies. Companies that are able to manage inventory effectively and implement prudent credit policies tend to have healthy cash flow and avoid liquidity problems. Additionally, making smart investment decisions based on thorough analysis also contributes to improved solvency. Companies that carefully consider risks and potential returns in investment decision-making have a healthier capital structure and are better able to meet their financial obligations. The findings provide a better understanding of the importance of effective financial management practices in enhancing the performance of companies in the manufacturing sector in Indonesia.